1.64 Interleukin-33 suppresses experimental arthritis through promoting Foxp3+ regulatory T-cells and type-2 immune responses in mice. (31st January 2014) - Biton, Jérôme; Thiolat, Allan; Khaleghparast Athari, Sara; Lemeiter, Delphine; Hervé, Roxane; Rogas, Stéphane; Levascot, Anais; Decker, Patrice; Girard, Jean-Philippe; Herbelin, André; Boissier, Marie-Christophe; Bessis, Natacha
Abstract : Background and Objectives: Interleukin (IL)-33 is a new member of the IL-1 family that exerts pleiotropic activities in innate and adaptive immunity. With its receptor ST2, they have newly emerged as key molecules strongly involved in several inflammatory and autoimmune disorders. Recent evidence suggests that the IL-33/ST2 axis is strongly involved in the pathophysiology of rheumatoid arthritis (RA). However in RA models, the role of IL-33 and its receptor is still controversial. We aimed at deciphering IL-33 mode of action after administration in an experimental model of RA, namely collagen-induced arthritis (CIA). Material and Methods: CIA was induced by immunisation of C57Bl/6 mice with type 2 collagen. IL‑33 was ip administrated in CIA mice and cells were analysed by flow cytometry on day 28 after CIA induction. Results: We show a previously unshown dramatic inhibition of mouse collagen-induced arthritis (CIA) development after repeated administration of IL-33. This therapeutic effect was related to an enhanced type-2 immune response, including the expansion of eosinophils, Th2 cells, innate type 2 lymphoid cells (ILC2, defined as CD25 + c-Kit + Lin - Sca-1 + ST2L + ) and an increase in Th2 cytokines levels in the serum of treated mice. Moreover, our work brings out the interplay between Treg and IL-33. Since IL-33 acts directly on Treg via ST2L, we showed that IL-33 treatment of CIA majors Treg frequency and increases the suppressive capacities of those cells. IL-33 also induces the emergence of a CD39 +/high Treg population in a ST2L dependant manner. Conclusions: In the light of our present study, IL-33 can exert powerful anti-inflammatory properties in CIA, integrating the establishment of a type-2 immune response, the expansion and the activation of Treg. Our study reveals an undescribed mechanism by which IL-33 inhibits arthritis development, thus updating and strengthening the crucial role of IL-33 in RA.